Practice-guided public health philosophy. (11th June 2021) - Folker, Anna Paldam; Lauridsen, Sigurd; Andersen, Martin; Kongsholm, Nana Cecilie; Varga, Somogy
Summary: Although highly relevant, philosophical theory and philosophical competences are rarely integrated in empirical public health research. We suggest a variant of applied philosophy that is valuable for the development and improvement of public health research. We call it practice-guided public health philosophy because: (i) research questions derive from public health challenges, i.e. real-life concerns that relate to the prevention of disease or the promotion of health and well-being, (ii) the ultimate test of success lies within an empirical framework aiming to improve public health practices and (iii) philosophers collaborate very closely with different kinds of empirical researchers in the different stages of the research process. Using examples from current public health projects at the National Institute of Public Health at the University of Southern Denmark, we outline three paradigmatic cases of practice-guided public health philosophy: (i) by using philosophy as an idea generator of empirical research, (ii) by using philosophy as a frame of reference for interpreting ethnographic data and (iii) by using philosophy as an explanatory resource for discussing survey and register data.